Cannabidiol inhibits SARS‐Cov‐2 spike (S) protein‐induced cytotoxicity and inflammation through a PPARγ‐dependent TLR4/NLRP3/Caspase‐1 signaling suppression in Caco‐2 cell line. (12th October 2021) - Corpetti, Chiara; Del Re, Alessandro; Seguella, Luisa; Palenca, Irene; Rurgo, Sara; De Conno, Barbara; Pesce, Marcella; Sarnelli, Giovanni; Esposito, Giuseppe
Abstract : Given the abundancy of angiotensin converting enzyme 2 (ACE‐2) receptors density, beyond the lung, the intestine is considered as an alternative site of infection and replication for severe acute respiratory syndrome by coronavirus type 2 (SARS‐CoV‐2). Cannabidiol (CBD) has recently been proposed in the management of coronavirus disease 2019 (COVID‐19) respiratory symptoms because of its anti‐inflammatory and immunomodulatory activity exerted in the lung. In this study, we demonstrated the in vitro PPAR‐γ‐dependent efficacy of CBD (10 −9 ‐10 −7 M) in preventing epithelial damage and hyperinflammatory response triggered by SARS‐CoV‐2 spike protein (SP) in a Caco‐2 cells. Immunoblot analysis revealed that CBD was able to reduce all the analyzed proinflammatory markers triggered by SP incubation, such as tool‐like receptor 4 (TLR‐4), ACE‐2, family members of Ras homologues A‐GTPase (RhoA‐GTPase), inflammasome complex (NLRP3), and Caspase‐1. CBD caused a parallel inhibition of interleukin 1 beta (IL‐1β), IL‐6, tumor necrosis factor alpha (TNF‐α), and IL‐18 by enzyme‐linked immunosorbent assay (ELISA) assay. By immunofluorescence analysis, we observed increased expression of tight‐junction proteins and restoration of transepithelial electrical resistance (TEER) following CBD treatment, as well as the rescue of fluorescein isothiocyanate (FITC)–dextran permeability induced by SP. Our data indicate, in conclusion, that CBD is a powerful inhibitor of SP protein enterotoxicity in vitro.